Comparison of tramadol and lornoxicam for the prevention of postoperative catheter-related bladder discomfort: a randomized controlled trial - Xin Liao; Min Xie; Shuying Li; Xiaolan Yu (Perioperative Medicine, 2023)
Abstract Background Catheter-related bladder discomfort (CRBD is a painful complication of intraoperative urinary catheterization after anaesthesia. We conducted this study to compare the effect of tramadol and lornoxicam for the prevention of postoperative CRBD. Methods One-hundred twenty patients (aged 18–60 years, ASA physical status 1–2, undergoing elective uterine surgery requiring intraoperative urinary catheterization were randomly divided into three groups with 40 patients in each group. Group T received 1.5 mg/kg tramadol, group L received 8-mg lornoxicam, and group C received normal saline. The study drugs were administered intravenously at the end of the surgery. The incidence and severity of CRBD were reported at 0, 1, 2, and 6 h after arrival at the postanaesthesia care unit (PACU). Results The incidence of CRBD was significantly lower in groups T and L than in group C at 1, 2, and 6 h after surgery. The incidence of moderate to severe CRBD was also significantly lower in groups T and L than in group C at 0, 1, and 2 h after surgery. The severity of CRBD reported as mild, moderate, and severe was reduced in groups T and L compared with group C at most times after surgery. Group T had a higher incidence of nausea than group C, and there were no differences in dizziness, drowsiness, or vomit among the three groups. Conclusions Tramadol and lornoxicam administered intravenously at the end of the surgery were both effective in preventing the incidence and severity of CRBD after uterine surgery. However, tramadol increased the incidence of nausea compared with saline, but there was no difference between tramadol and lornoxicam. Trial registration ChiCTR2100052003. Registered on 12/10/2021.